2016
DOI: 10.1109/tcpmt.2016.2619939
|View full text |Cite
|
Sign up to set email alerts
|

Thermally “<italic>Smart</italic>” Characteristics of Nanofluids in Parallel Microchannel Systems to Mitigate Hot Spots in MEMS

Abstract: Mitigation of 'hot spots' in MEMS employing in-situ microchannel systems requires a comprehensive picture of the maldistribution of the working fluid and uniformity of cooling within the same. In this article, detailed simulations employing parallel micro channel systems with specialized manifold-channel configurations i.e. U, I and Z have been performed. Eulerian- GHz quad core processor) under various processor load conditions has been studied and evidence of enhanced cooling of hot spots has been obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Employing nanofluids as coolants is a good option to achieve uniform cooling of microelectronic devices and modules thereby making the analysis of the performance of variant nanofluids as coolants important. Since nanofluids are reported to act as smart fluids in micro flow paths [21,22], it is essential to know the hydro dynamic behaviour of the same for design of the pumping system. Comparison of hydrodynamic characteristics of different types of nanofluids in PMCS has been illustrated in fig.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…Employing nanofluids as coolants is a good option to achieve uniform cooling of microelectronic devices and modules thereby making the analysis of the performance of variant nanofluids as coolants important. Since nanofluids are reported to act as smart fluids in micro flow paths [21,22], it is essential to know the hydro dynamic behaviour of the same for design of the pumping system. Comparison of hydrodynamic characteristics of different types of nanofluids in PMCS has been illustrated in fig.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In reality, single phase fluids such as water are not expected to fulfil the cooling requirements. Employing nanofluids as working fluid is one of the best alternative solutions to attain enhanced cooling as these fluids demonstrate smart features [21,22] due to particle migration which enhances heat transfer characteristics.…”
Section: Thermal Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Among the several proposed methods, employing efficient heat transfer fluids such as nanofluids is one of the best methods, as reported by Li and Kleinstreuer [14], Escher et al [15] and Lee and Mudawar [16]. Employing nanofluids as working fluid in such complex flow domains not only improves cooling but also uniformity of cooling (Maganti et al [17]) because of smart nature of nanofluids at high temperatures, reported by Das et al [18]. In addition, there is the challenge of designing such effective cooling systems as in reality heat emitted by microelectronic devices will never be uniform and leads to further non-uniform cooling of microelectronic devices (Maganti et al [17] and Cho et al [19]).…”
Section: Introductionmentioning
confidence: 99%